HUBUNGAN BERAT BADAN DENGAN SUHU TUBUH BAYI BARU LAHIR DI RUANG PERINATOLOGI RSUD DR. SOEBANDI KABUPATEN JEMBER - Novi Andari; Nikmatur Rohmah; Zuhrotul Eka Yulis Anggraeni (PROFESSIONAL HEALTH JOURNAL, 2022)
Introduction: Baby's body temperature is an emergency in newborns. Most infant deaths are caused by changes in body temperature at birth, namely hypothermia. The purpose of this study was to determine the relationship between birth weight and body temperature of newborns. Methods: The research design was correlational with a cross-sectional approach. The population of this study were newborns in the Perinatology Room, RSD dr. Soebandi Jember. The sample in this study were 78 infants using simple random sampling. Data analysis in this research uses Product Moment Correlation. Results: The results showed that p value = 0.035, this indicates that there is a relationship between body weight and body temperature of newborns in the Perinatology Room of RSUD dr. Soebandi, Jember Regency. The OR value = 0.651, therefore, the body weight has a risk of 0.6 times causing the baby to experience hypothermia. This is influenced by the baby's age, gender, and the distance between births and previous children. Conclusion: Babies with LBW are at risk of causing babies to experience hypothermia. Suggestion: The recommendation of this study is that nurses should be able to observe changes in temperature in infants, especially when moving rooms, from the delivery room to the treatment room, and continue to closely observe the baby's body temperature, especially 6 hours immediately after delivery.